The role of chloride ions during the formation of akaganéite revisited - Scheck, J.; Lemke, T.; Gebauer, Denis (2015)
© 2015 by the authors; licensee MDPI, Basel, Switzerland.Iron(III) hydrolysis in the presence of chloride ions yields akaganéite, an iron oxyhydroxide mineral with a tunnel structure stabilized by the inclusion of chloride. Yet, the interactions of this anion with the iron oxyhydroxide precursors occurring during the hydrolysis process, as well as its mechanistic role during the formation of a solid phase are debated. Using a potentiometric titration assay in combination with a chloride ion-selective electrode, we have monitored the binding of chloride ions to nascent iron oxyhydroxides. Our results are consistent with earlier studies reporting that chloride ions bind to early occurring iron complexes. In addition, the data suggests that they are displaced with the onset of oxolation. Chloride ions in the akaganéite structure must be considered as remnants from the early stages of precipitation, as they do not influence the basic mechanism, or the kinetics of the hydrolysis reactions. The structure-directing role of chloride is based upon the early stages of the reaction. The presence of chloride in the tunnel-structure of akagenéite is due to a relatively strong binding to the earliest iron oxyhydroxide precursors, whereas it plays a rather passive role during the later stages of precipitation.